PENGARUH IMBANGAN SUSU UHT DAN JUS KURMA TERHADAP JUMLAH BAKTERI, TOTAL YEAST DAN AKTIVITAS ANTIOKSIDAN PADA PRODUK SUSU KURMA - Rizkika, Meisha Ayudia Rahma; Wulandari, Eka; Utama, Dicky Tri (Jurnal Teknologi Hasil Peternakan, 2023)
Ultra High Temperature (UHT) milk or packaged milk is milk that is processed through heating that exceeds the pasteurization process, which refers to a certain combination of time and temperature to obtain a sterile commercial product. The addition of date juice to date milk products will cause changes both physically, chemically, and microbiologically. This study aims to determine the best concentration of date palm juice on date milk products with the lowest number of bacteria and total yeast and the highest antioxidant activity. This research was conducted in January 2023 at the Laboratory of Animal Product Processing Technology, Padjadjaran University, Sumedang. The study was conducted experimentally with a completely randomized design (CRD) using 3 treatments and 6 replications with the percentage of date juices consisting of P1 (10%), P2 (20%) and P3 (30%). The research data were analyzed using analysis of variance and Duncan's multiple range test for the parameters of the number of bacteria, total yeast and antioxidant activity. The results showed that the addition of 30% date palm juice had the best effect on the number of bacteria and total yeast, and antioxidant activity. The best addition of date palm juice is at a concentration of 10% with total bacteria 4,54× 10 4 total yeast 3,25× 10 5 dan antioxidant activity 242,63 ppm.